Acute mutism: a useful lesson. Issue 1 (20th July 2010) - Maguire, Melissa; Seidi, Osheik; Baker, Mark; Gupta, Arun; Muwanga, Cyrus
Abstract : Broca's aphasia may manifest as mutism in some patients. Mutism may be misinterpreted as part of a depressive illness in patients with a psychiatric history. We report on a patient presenting with acute mutism who had a history of amphetamine and cannabis abuse and was later found to have sustained an infarct of the dorsolateral frontal cortex. Recognition of this mode of presentation will aid early diagnosis and treatment.